The impact of COVID on the development of HRM in public service: Lessons from international practice - Zoltán Hazafi; Edit Kajtár (University American College Skopje, 2021)
COVID has had an immense impact on HRM. The aim of this Paper is to examine international responses and detect best practices. We analyse a variety of methods, techniques, trends and ideas from all over the world. Insights from Hungary, Austria, Germany, Spain, Italy, Portugal, the Netherlands, the United Kingdom, Ireland, the US and Canada are considered. Work has been transported to virtual space. Home office has grown into being the engine of public service development. It is likely that the future will be characterised by hybrid models. Online operation is intertwined with numerous issues, such as: simplification and increased efficiency of procedures, legal regulation of the transformation and data protection. Numerous questions require our answer as regards the use of virtual space: How will teamwork function? What adjustments are required in learning and development schemes? What is the new role of leaders? How can we assure mental health? How do we promote resilience? Another trend concerns digitalisation of recruitment and selection. Digitalisation is spilling over to the neighbouring areas, such as job branding, mobility management and onboarding. How will the post-COVID era look like? The scale of HRM changes ranges from mere adjustment to paradigm shift. Areas of utmost importance include: consequences of accelerated digital transformation, growing importance of IT skills, new methodology for learning and development, demand for resiliency, sustainable development, efficiency, social dialogue as well as restoration of trust between employer and employee.
Keywords: 330; COVID; crisis; HR; digitalisation; education; work; atypical; resilience